Initial Method for Characterization of Tympanic Membrane Drug Permeability in Human Temporal Bones In Situ - Early, Samuel; Yang, Rong; Li, Xiyu; Zhang, Zipei; van der Valk, Jens C.; Ma, Xiaojie; Kohane, Daniel S.; Stankovic, Konstantina M. (Frontiers in Neurology, 2021)
Background and Introduction: Acute otitis media is the most common reason for a visit to the pediatrician, often requiring systemic administration of oral antibiotics. Local drug therapy applied to the middle ear could avoid side effects associated with systemic antibiotic administration, however in the majority of patients this would require drugs to diffuse across an intact tympanic membrane. Experimental methods for testing trans-tympanic drug flux in human tissues in situ would be highly valuable to guide drug therapy development for local drug delivery to the middle ear. Materials and Methods: A total of 30 cadaveric human temporal bones were characterized by trans-tympanic impedance testing to determine how steps in tissue processing and storage might impact intactness of the tympanic membrane and thus suitability for use in studies of trans-tympanic drug flux. Ciprofloxacin drug solutions of varying concentrations were then applied to the lateral surface of the tympanic membrane in eight samples, and middle ear aspirate was collected over the following 48 h to evaluate trans-tympanic flux to the middle ear. Results: Tissue processing steps that involved extensive tissue manipulation were consistently associated with evidence of microperforations in the tympanic membrane tissue. Maintaining the tympanic membrane in situ within the temporal bone, while using an otologic drill to obtain transmastoid access to the middle ear, was demonstrated as a reliable, non-damaging technique for accessing both lateral and medial surfaces for trans-tympanic flux testing. Results in these bones demonstrated trans-tympanic flux of ciprofloxacin when administered at sufficiently high concentration. Discussion and Conclusion: The study describes key techniques and best practices, as well as pitfalls to avoid, in the development of a model for studying trans-tympanic drug flux in human temporal bones in situ. This model can be a valuable research tool in advancing progress toward eventual clinical studies for trans-tympanic drug delivery to the middle ear.